Effects of Individual Differences in Motor Imagery Ability on the Excitability of Spinal Neural Function - KADO, Naoki; NOMURA, Makoto; MAEDA, Takenobu; SUZUKI, Toshiaki (Rigaku ryoho kagaku, 2017)
[Purpose] This study examined whether motor imagery ability affects the excitability of the spinal neural function. [Subjects and Methods] We evaluated the effect of motor imagery of finger opposition movements with differing complexities on the excitability of spinal neural function using F-wave analysis. The subjects were 30 healthy adults who were divided into high and low motor imagery ability groups based on their responses to the Vividness of Movement Imagery Questionnaire (VMIQ). F-waves were recorded under the following four conditions: at rest; during motor imagery of opposition movement of the right thumb and index finger (task 1); during motor imagery of opposition movement of the right thumb and index, middle, ring, and little fingers (task 2); and during motor imagery of opposition movement of the right thumb and index, ring, middle, and little fingers (task 3). [Results] In the low motor imagery ability group, the amplitude ratio of F/M was significantly higher than that at rest during tasks 2 and 3. [Conclusion] The findings of the present study suggest that individual differences in motor imagery ability possibly influence the excitability of spinal neural function during motor imagery.